Mediation effect of psychological factors on betrayal trauma and physical health symptoms among young adults - Teli, Bilal A.; Bano, Samina; Paul, Mohd A. (International Journal Of Community Medicine And Public Health, 2022)
Background: Betrayal trauma theory postulates abuse perpetrated by a caregiver or someone close to the victim results in worse mental health and physical health problems than abuse perpetrated by a non caregiver. Hence the present study was designed to study the mediation effect of psychological factors on high betrayal trauma and physical health symptoms among young adults. Methods: young adults with history of trauma based on purposive were taken from Delhi. Out of 200 young adults, 100 were high betrayal traumas and 100 were low betrayal traumas with age group ranged from 20-30 years. In order to identify high betrayal trauma and low betrayal trauma the brief betrayal trauma survey, followed by Toronto alexithymia scale, trauma symptom checklist-40, Pennebaker inventory of limbic languidness and socio-demographic data sheet. Results: The present study studied the mediation analyses and found that sexual abuse and sexual problem were mediates the association between high betrayal trauma and physical health problem. Conclusions: The mediation effect by sexual abuse trauma and sexual problem was reported on high betrayal trauma and physical health symptoms It highlights to inform the health professionals about the diverse range of symptoms associated with betrayal trauma and highlights the urgency of immediate intervention of betrayal trauma and helps the health professionals in awareness of connection among betrayal trauma, psychological difficulties, and physical health complaints and make appropriate assessments and referrals.